PREMARITAL PREGNANCY FOR PREFECTIONAL TEENS LAW AND PSYCHOLOGY - SHOFIATUL JANNAH; HUMAIDI DIPLAL; FITRAH SUGIARTO (Universitas Islam Negeri Mataram, 2022)
The phenomenon of pregnancy out of wedlock often occurs among teenagers; this happens due to many factors which, if generalized, are a combination of the consequences of promiscuity and the lack of parental observation of their child's association. so that without strict supervision, adolescents will do whatever is considered suitable by themselves without thinking about the consequences that will arise from their behavior. This research is a literature study with a qualitative type of research, namely observing premarital pregnant marriages and reviewing community legal compliance with applicable laws in Indonesia, especially regarding how pregnant marriage is legal and the impact on pregnant marriage actors. The results of this study are premarital pregnancy has a more dominant effect on women. Women often get legal injustice, so there is a need for clear and detailed special regulations regarding premarital pregnancy.